x/2+3=3
-3 -3 (subtract 3 from both sides)
x/2=0
x=0
2006-10-21 14:47:57
·
answer #1
·
answered by Anna 2
·
2⤊
0⤋
X/2 +3 = 3
Move first 3 to the right side, by adding -3 to both sides.
X/2 -3 +3 = 3 -3
X/2 = 0
Move the 2 to the right side, by multiplying both sides by 2.
2( X/2) = 0* 2 =0
2 divided by 2 is 1
(2/2)*X =0
1*X =0
X=0
2006-10-21 14:53:32
·
answer #2
·
answered by Austin Semiconductor 5
·
0⤊
0⤋
x=0
0 divided by anything is zero so 0/2=0 0+3=3
0/2+3=3
2006-10-21 14:48:31
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
x/2 + 3 = 3
Subtract 3 from both sides
x/2 = 0
Multiply both sides by 2
x = 2(0)
x = 0
2006-10-21 14:48:46
·
answer #4
·
answered by MsMath 7
·
0⤊
0⤋
Subtract 3 from both sides to get
x/2 = 0,
which yields x = 0.
2006-10-21 14:55:53
·
answer #5
·
answered by steiner1745 7
·
0⤊
0⤋
x / 2 + 3 = 3
x / 2 = 3 - 3
x / 2 = 0
x = 0 x 2
x = 0
2006-10-22 05:15:11
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x/2 + 3 = 3
x/2 + 3 - 3 = 3 - 3
x/2 + 0 = 0
x/2 = 0
x/2 * 2 = 0 * 2 =
x * 1 = 0
x = 0 / 1
x = 0
2006-10-21 15:12:00
·
answer #7
·
answered by Dr. J. 6
·
0⤊
0⤋
Since 3 = 3 by the reflexive axiom, x = 0 is the only unique solution.
2006-10-21 20:17:02
·
answer #8
·
answered by Jerry M 3
·
0⤊
0⤋
x/2 + 3 = 3
First we need to isolate x.
So subtract 3 from each side.
x/2 + 3 - 3 = 3 - 3
x/2 = 0
Multiply both sides by 2
(x/2)2 = 0(2)
x = 0
Any questions?
2006-10-21 15:57:11
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
x/2+3=3
x/2+3-3=3-3 <--get rid of the 3
x/2=0
x/2*2=0*2 <--get rid of the 2
x=0
2006-10-21 14:48:12
·
answer #10
·
answered by ♥Jenny! 3
·
0⤊
0⤋